PENGGUNAAN EKSTRAK DAUN MIMBA UNTUK MENGENDALIKAN SERANGAN CENDAWAN Alternaria porrii PADA BAWANG MERAH - Agung Kurniawan (Agro 15 UMY 076, 2015)
*76 The research about utilizing neem leaf extract to control Alternaria porrii on onion purposed to determine the aplication and concentration of neem leaf extract for control Alternaria porrii on onion and to know the interaction between it. The research was conducted at tamantirto, bantul, yogyakarta. Research arranged in experiment method with two steps, first is isolation and characterization of Alternaria porrii from field and second is the aplication at fields in complete randomized blok design with two factor, first is the methode of aplication and the second is the concentration were bit of 9 combinations neem leaf extract that is soaked concentration 0%, 10% and 20%. Sprayed concentration 0%,10% and 20%. Soaked+sprayed concentration 0%, 10% and 20%. The result shows that neem leaf extract treatment concentration 10% and 20% was significantly different at weeks 4 and 5. Week 7 was significantly different in aplication sprayed treatment. In weeks 6 and 8 was not significantly different at all treatment to control the intencity of Alternaria porrii in onion.